The training and accreditation of teachers for English medium instruction: an overview of practice in European universities - O'Dowd, Robert (International journal of bilingual education and bilingualism, 2018)
English-medium instruction (EMI) is widely believed in higher education contexts to support the internationalisation of universities, to make study programmes more accessible to international students and to enhance the international prestige of academic staff. However, the pressure on European institutions to offer subjects through English raises the issue of whether a sufficient number of teachers are capable of teaching their subject content through the language. Although some recent research has found that EMI programme directors are largely satisfied with the English proficiency of their teaching staff (Wächter and Maiworm, 2014. English-Taught Programmes in European Higher Education. The State of Play in 2014. Bonn: Lemmens. Accessed November 17, 2017. http://www.aca-secretariat.be/fileadmin/aca_docs/images/members/ACA-2015_English_Taught_01.pdf ), other reviews of current practice have highlighted a need for a more structured and rigorous approach to the language and methodology training of teachers (Dearden 2015. "English as a Medium of Instruction - A Growing Global Phenomenon." Accessed 17 November 2017. http://www.britishcouncil.org/education/ihe/knowledge-centre/english-language-higher-education/report-english-medium-instruction ; Halbach and Lázaro 2015. "La acreditación del nivel de lengua inglesa en las universidades españolas: Actualización 2015." Accessed November 17, 2017. http://www.britishcouncil.es/sites/britishcouncil.es/files/british-co uncil-la-acreditacion-del-nivel-de-lengua-inglesa.pdf ). This article reports on the findings of a survey of 70 European universities carried out in 2014-2015 which provides an overview of current practices in the training and accreditation of university teachers in EMI. The findings reveal a very eclectic range of approaches to training and accrediting teachers working in this area.